Das TrEffeR-Projekt der Bundesagentur für Arbeit: die Wirkung von Maßnahmen aktiver Arbeitsmarktpolitik - Gesine Stephan; Susanne Rässler; Torben Schewe (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– This paper presents the project 'Treatment Effects and Prediction' (TrEffeR) of the Federal Employment Agency (Bundesagentur für Arbeit - BA). One of the tasks of the project is to provide estimates of the effectiveness of active labor market policy measures for management purposes. The results of a regionally differentiated retrospective analysis support employment agencies continuously in the ex post identification of strengths and weaknesses in the allocation of measures. The microdata set constructed for the project can also be used to gain an overall impression of the effect of labour market policy instruments: On the basis of the new database the paper examines if participation helped to avoid further unemployment for individuals who took up a measure in September 2002.
Keywords: 330; Arbeitsmarktpolitik; Wirkungsforschung; Datenbank; Bundesagentur für Arbeit